On the nature of morphological awareness and vocabulary knowledge in school-age English-Japanese bilingual and monolingual children - Hayashi, Y (2012)
Morphological awareness and vocabulary knowledge are two (among many) components of multi-faceted word knowledge critical for language development and ultimately, academic performance, as they strongly correlate with other essential, literacy-related skills, such as spelling, writing and reading comprehension (Ramirez, Chen, Geva & Kiefer, 2010). Developing these types of knowledge is a non-linear process for school-age children: morphological awareness, in particular, involves long-term learning towards a full mastery beginning in mid-dle childhood and continuing through adolescence. Such learning processes can pose significant challenges especially for children attending a school entirely in a second language (L2) while speaking, as a first language (L1), a language which is ethno-linguistically minority in status in the larger (L2) society. Despite globally growing populations of L2 children in school settings, little is known about the nature of morphological/vocabulary knowledge in one language, relative to the other, especially when children are learning two typologically distant languages with different writing systems. The current study, situated within the theoretical framework of multicompetence (Cook, 2003), set out to investigate specific aspects of vocabulary knowledge and morphological awareness in different groups of English- and Japanese-speaking monolingual and bilingual children, whilst also examining the extent to which English morphological awareness influences/or is influenced by Japanese morphological awareness among the bilingual sample. The purpose of the study is largely three-fold. One was to examine the children’s ability to understand and express a connection between a word and its meaning. The former taps into receptive vocabulary knowledge, whereas the latter expressive vocabulary knowledge. Two vocabulary tests were administered to three groups of children per language: two bilingual groups (24 Japanese learners of English as a Second Language (ESL) and 21 learners of Japanese as a Heritage Language (JHL)) and a group of 25 English Language Monolinguals (ELMs) (English); and ESLs, JHLs and a group of 27 Japanese language Monolinguals (JLMs) (Japanese). The second purpose was to investigate the children’s ability to identify morphemes included in a word and also to produce inflectional and derivational forms of a word, using two morphological tasks per language – a Word Segmentation (WS) task and a Word Analogy (WA) task. Lastly, the current study examined, through statistical analyses, the nature of an association between morphological awareness and vocabulary knowledge in each language, and also whether morphological awareness in one language could act as a significant predictor of morphological awareness in the other, i.e., cross-linguistic influence. Four key findings were obtained. First, the patterns in which each group demonstrated vocabulary knowledge through English tests contrasted with the pattern observed in the Japanese results. In English, the ESL group scored more highly on the receptive test than the expressive test, whereas the reverse pattern was the case for the ELM group. The JHL group yielded comparable scores across tests. In Japanese, in contrast, all three groups (ESL/JHL/JLM) scored more highly on the expressive test than on the receptive test. Second, all groups of children typically demonstrated higher degrees of an awareness of inflectional morphemes than of derivational morphemes in the English morphological tasks (both the WS and WA tasks) and the Japanese WA task. A slightly different pattern was observed in the Japanese WS task, where the performances of ESL and JLM children were not sensitive to morpheme type, whereas the JHL group yielded higher scores on the inflectional morphemes than the root morphemes. As regards the relationship between morphological awareness and vocabulary knowledge in each language, in English, it was the ability to produce morphologically complex items, as opposed to recognising morphemes, that was positively related to vocabulary knowledge in all three groups (ESLs, JHLs & ELMs). In Japanese, in contrast, both morpheme recognition and production were positively related to vocabulary knowledge in all Japanese-speaking groups (ESLs, JHLs & JLMs). Lastly, the bilingual data identified a reciprocal nature of morphological transfer (Japanese -> English) only in the ESL group. More specifically, the ESL children’s ability to identify morphemes in Japanese words through segmentation may have a positive influence on the ability to produce English inflectional and derivational items. The latter ability is, in addition, likely to play a positive role in its Japanese equivalent, namely, the ability to produce Japanese inflectional and derivational items. No transfer effects were established in either direction for the JHL group. These within-language and cross-linguistic investigations of the nature of, and the relationship between morphological awareness and vocabulary knowledge are discussed in terms of the existing evidence in the literature (e.g., Carlisle, 2000; Ramirez at al.,2010) and are graphically illustrated via the integration continuum based on the notion of multicompetence (Cook, 2003). Several limitations of the current study are reviewed and discussed, fol-lowed by the Conclusion chapter, where the unique contribution of the current study to the literature is revisited, together with a brief remark about its indirect links with the field of educational research in Japan and suggestions for future research.